Effect of drying treatments on texture and color of vegetables (pumpkin and green pepper). - Guiné, Raquel (2012)
The present work evaluates the effect of different drying treatments on the color and textural attributes of green bell peppers and pumpkin, which were dried using two different methods: air drying and freeze-drying. The treatments in air drying were carried out at 30 ºC and 70 ºC. From the results it is possible to conclude that the increase in drying temperature reduced drastically the hardness of green peppers and the freeze drying had an intermediate effect between vegetables dried at 30 ºC and 70 ºC. Moreover, the springiness was higher in dried green peppers but an opposite effect was observed on chewiness. With respect to pumpkin, it was not found any dependence between the fibre orientation and the hardness of the fresh vegetable. In addition, increasing temperature from 30 ºC to 70 ºC particularly reduced the hardness and the chewiness of dried product and maintained cohesiveness and springiness approximately constant. Regarding the color, it was possible to conclude that air drying at 30 ºC produced small changes in color of green pepper whereas air drying at 70 ºC and freeze drying originated more intense color changes. The increase of temperature on air drying augmented the color saturation of dried pumpkin while decreased the hue angle by a linear relationship. In addition, the chroma of dried pumpkin decreased significantly with the freeze drying, while the hue angle was maintained constant as compared with the fresh vegetable.